2016
DOI: 10.1136/jclinpath-2016-203715
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of immunophenotypically aberrant CD34+ myeloid progenitors is frequent in bone marrow of patients with myelodysplastic syndromes and myelodysplastic/myeloproliferative neoplasms treated with hypomethylating agents

Abstract: These findings show the difficulty in eradicating neoplastic myeloid precursors by HMA therapy, thereby resulting in ultimate treatment failure in most patients. Achieving immunophenotypic improvement helps to identify patients who may benefit from continuous HMA treatment. HSCT provides a potential cure for these patients by replenishing BM with normal haematopoietic stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Just those with cytogenetic remission presented normal CD34 + cells. 29 This is consistent with our finding of the persistence of phenotypic abnormalities and thus, patients reach transplantation with a remaining abnormal clone. All patients with progressive disease had CD7 + myeloid progenitors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Just those with cytogenetic remission presented normal CD34 + cells. 29 This is consistent with our finding of the persistence of phenotypic abnormalities and thus, patients reach transplantation with a remaining abnormal clone. All patients with progressive disease had CD7 + myeloid progenitors.…”
Section: Discussionsupporting
confidence: 93%
“…This finding correlated with clinical and genetic response. Just those with cytogenetic remission presented normal CD34 + cells 29 . This is consistent with our finding of the persistence of phenotypic abnormalities and thus, patients reach transplantation with a remaining abnormal clone.…”
Section: Discussionsupporting
confidence: 92%
“…It has been observed that osteosarcoma tumors are highly metastatic and have a high recurrence rate ( 2 ). Despite a number of proposed clinical strategies, the prognosis for patients with osteosarcoma remains poor as there is limited understanding of the disease and few effective therapeutic targets have been identified ( 3 , 4 ). Osteosarcoma cells also have a high degree of apoptotic resistance ( 5 , 6 ), therefore, it is necessary to investigate the underlying mechanisms behind their angiogenesis and migration to better understand the pathological processes of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Bone neoplasm is typical systemic malignant disease, which mainly leads to common symptoms of bone and joint pain and fatigue in patients (1,2). Osteosarcoma is the most common cancer-caused dead and the prognosis remains incompletely understand due to the paucity of effective therapeutic targets that significantly influences quality of life and mean survival rate of the patients with osteosarcoma (3,4). Clinicopathological and molecular correlations explain the role of bone marrow microvessel density (MVD) and plasma angiogenic factors in myeloproliferative neoplasms and highlight the strong correlation of MVD with plasma angiogenic factors, JAK2 mutant allele burden, and bone marrow fibrosis in myeloproliferative neoplasms (5).…”
Section: Introductionmentioning
confidence: 99%